Adolescents' representations of close relationships in the context of parental migration: an exploratory study from Ecuador. Issue 3 (10th August 2020) - Jerves, Elena Monserrath; De Haene, Lucia; Rober, Peter; Enzlin, Paul
Abstract : Purpose: The purpose of this study is to examine the association between parental migration and adolescents' styles of close relationships with parents, friends and romantic partners. Design/methodology/approach: In total, 197 adolescents from Cuenca (Ecuador) participated in the study, of which 35% reported a background of parental migration. The Behavioral Systems Questionnaire was used to assess participants' relational styles. Findings: The study reveals that, although parental migration is associated with the development of lower secure styles for parents and friends, it is not associated with the development of insecure styles. Moreover, parental migration does not appear to be associated with the development of romantic styles. Based on the differential impact of the migration of one or two parents, the migration of two parents appeared to have a stronger association with lower secure styles. Originality/value: The results are discussed in light of the socio-cultural context in which parental migration occurs in Ecuador, which may offer clue variables in shaping the relational styles of adolescents. The study addresses an important consequence of migration focusing on a scarce studies group, adolescents who stay in their home country while their parents migrate. Moreover, its main findings challenge the preconceptions that parent-child separations necessarily involve a direct negative impact on relational functioning.